Maternal thyroid function, postnatal depression, the intake and status of iodine, selenium, and iron in postpartum women and their infants : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Science at Massey University, Manawatū, New Zealand - Jin, Ying (Massey University, 2021)
Background: Thyroid dysfunction is a common health issue in women, with a higher prevalence found in postpartum women. Postnatal depression (PND) is a maternal health issue which can exacerbate negative health effects on their newborns. Iodine, selenium, and iron are three essential nutrients for the synthesis of thyroid hormones. Historically, dietary insufficiency of iodine and selenium exist in New Zealand. To improve iodine status, the New Zealand government introduced mandatory fortification of bread with iodised salt (2009), and recommended iodine supplementation (150 µg/day) for all pregnant and breastfeeding women (2010). Mostly, the iron status of postpartum women in New Zealand is rarely medically examined, unless high levels of blood loss during childbirth are recorded. Objectives: The overall aim of this PhD thesis was to investigate maternal thyroid function, postnatal depression, and the intake and status of iodine, selenium and iron in mothers and infants during their first postpartum year. Method: This observational longitudinal cohort study was conducted in Palmerston North, New Zealand, from June 2016 to December 2017. Mother-infant pairs attended study visits at three, six and twelve months postpartum (3MPP, 6MPP, and 12MPP). Online questionnaires investigated maternal iodine knowledge, supplement use, mode of infant feeding, and sociodemographic characteristics. Weighed four-day dietary diary, with urine/blood/breastmilk samples, were taken to measure maternal iodine, selenium, and iron intake/status. Infant iodine and selenium concentrations were determined in spot urine samples. The Edinburgh Postnatal Depression Scale was used to screen for PND. At 6MPP, serum thyroid hormones [free triiodothyronine, free thyroxine, thyroid stimulating hormone (TSH), thyroglobulin (Tg) and anti-Tg and thyroid peroxidase antibodies] and thyroid volume were measured. Results: At 3MPP, 87 breastfeeding mother-infant pairs were recruited, followed up at 6MPP (n = 78) and 12MPP (n = 71). At 6MPP, 18% of women had thyroid dysfunction. Median total thyroid volume was 6.1 mL. Median (p25, p75) Tg was 11.4 (8.6, 18.6) µg/L, above 10 µg/L. Median maternal plasma selenium was 105.8 (95.6, 115.3) µg/L; 23% (17/74) being below 95 µg/L; with 4% of women experiencing iron deficiency without anaemia. Women with marginally lower plasma selenium were 1.14% times more likely to have abnormal TSH concentrations. Over the first postpartum year, maternal median urinary iodine concentration (MUIC) was 82 (46, 157) µg/L, 85 (43, 134) µg/L, and 95 (51, 169) µg/L, all below 100 µg/L; median BMIC was 69 (52, 119) µg/L, 59 (39, 108) µg/L, and 35 (26, 54) µg/L, all below the recommended 75 µg/L. Median maternal iodine intake was 151 (99, 285) µg/day, with 58% below the Estimated Average Requirement (EAR). At 3MPP, 46% of women took iodine-containing supplements, this reduced to 11% at 6MPP, and 6% at 12MPP. Women who used iodine-containing supplements had significantly higher MUIC (111 vs 68 µg/L) and BMIC (84 vs 62 µg/L) than non-users (P < 0.001). Infants fed by women using iodine-containing supplements had a higher MUIC (150 vs 86 µg/L, P = 0.036) than those of non-users. Infant MUIC at 3MPP [115 (69, 182) µg/L] and 6MPP [120 (60, 196) µg/L] were below 125 µg/L (suggested cut-point for iodine adequacy in infants). Median maternal selenium intake was 62 (51, 85) µg/day and 56% had intakes below the EAR. Median infant selenium intakes at 3MPP and 6MPP were 9 and 8 µg/day. Median maternal urinary selenium concentrations were 22, 22, and 26 µg/L across three time points, respectively. The highest prevalence of minor depression was observed in women with mean plasma selenium at 106 µg/L. Conclusions: A high prevalence of thyroid dysfunction was observed in a cohort of postpartum women who were iodine deficient, with suboptimal selenium intake, but having mostly adequate iron status. Women with low plasma selenium were likely to experience thyroid dysfunction. Iodine deficiency of lactating women remains, particularly for those who did not use iodine-containing supplements. The low use of iodine-containing supplements is concerning during later breastfeeding. Maternal selenium intake/status was suboptimal. Relation between selenium status and risk of PND was inconclusive. Iodine/selenium intake and status of infants were suboptimal.
Keywords: Mothers; Infants; Nutrition; Thyroid gland; Diseases; Postpartum depression; New Zealand; 321005 Public health nutrition